1980
DOI: 10.1063/1.439973
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of tensorial interactions determined from two-dimensional NMR powder spectra

Abstract: Methods are described for determining the mutual orientation of molecular interaction tensors based on twodimensional NMR powder spectra. Necessary conditions are derived under which this determination can be made, procedures for the computation and analysis of 2D powder spectra are indicated, and a technique for the construction of ridge plots is worked out. Chemical shift resolved dipolar powder spectra provide an easily interpreted representation of the mutual orientation of chemical shielding and dipolar c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
2

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(115 citation statements)
references
References 34 publications
2
111
0
2
Order By: Relevance
“…If the magnitude of the latter interaction is on the order of the 1 4~ Zeeman interaction, the high-field approximation breaks down and the Zeeman spin functions mix, introducing distortions in the nmr lineshape calculated from eq. [8]. Stoll et al (29) have shown that provided the ratio of the 14N Larmor frequency, vN = yNBo/2.rr, to the 14N quadrupolar coupling constant, X, is greater than 4, the high-field approximation results in relatively small errors when calculating the lineshape.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…If the magnitude of the latter interaction is on the order of the 1 4~ Zeeman interaction, the high-field approximation breaks down and the Zeeman spin functions mix, introducing distortions in the nmr lineshape calculated from eq. [8]. Stoll et al (29) have shown that provided the ratio of the 14N Larmor frequency, vN = yNBo/2.rr, to the 14N quadrupolar coupling constant, X, is greater than 4, the high-field approximation results in relatively small errors when calculating the lineshape.…”
Section: Theorymentioning
confidence: 99%
“…Recently, however, there have been several reports of determination of the orientation of the shielding tensor from a single experiment (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). This has been accomplished by studying an isolated spin pair where dipolar coupling exists between the two nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The principal challenge in powder nrnr is to extract these observables from a powder spectrum or to devise ingenious experiments that allow one to separate these interactions so that they can be observed individually (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the tensors from single crystals of model compounds could provide only an approximate (k5-10") orientation of the tensor with respect to the molecular frame. With the advent of relating the chemical shift tensor to a dipolar interaction that has a unique axis fixed in the molecular frame (Linder et al, 1980) it is possible to consider a determination of the chemical shift tensor orientation for specific sites in the molecule of interest. This was first achieved with "N backbone sites in gramicidin in 1989 (Teng & Cross, 1989), and other tensors have been determined since Wang et al, 1992).…”
mentioning
confidence: 99%